Numerical investigation of flow past a rotationally oscillating square cylinder - N. K. Singh, Nitesh Kumar (International Journal of Advanced Science and Technology, 2020)
Numerical simulations are performed for the flow past a square cylinder rotationally oscillating about its axis using ANSYS FLUENT 19R1 package. Investigations are done with frequency ratios Fr (0.8, 1.0, 1.2, 1.4, 1.6, and 2.0) and maximum oscillation amplitudes (100, 200, 400, and 500) with two Reynolds numbers 100 and 400, respectively. Preliminary analysis is done considering the cylinder stationary at Re 100 and different domain sizes. Domain size of 20, 40, and 60 are chosen after comparing it with previous work and that is used for the rotational oscillation case. The results are obtained with non-dimensional lift and drag force, velocity and pressure contours and velocity vector plots. At a fixed frequency ratio, a general increase in drag and lift coefficients as well increase in local fluctuations is observed with an increase in angular amplitude from 100-500. When the oscillation amplitude is kept constant, an increase in frequency ratio leads to more random fluctuations in drag and lift coefficients. A large increase in drag and lift coefficients is found when the Reynolds number is increased from 100 to 400, although the frequency ratio (Fr) and oscillation amplitude (θo) are kept constant. It is observed through velocity and pressure contour plots that vortex formation length near the cylinder increases at higher Re. Velocity vector plots show fluid flow behavior near the cylinder. Variation of non-dimensional drag and lift forces are also presented for higher Fr (2.0 and 3.0) with θ0 (100, 200, and 300, respectively). The results underline the need to improve the quality of mesh for the cases of higher Fr and θo. Rotational oscillation to the cylinder, being an active method to control the drag forces on the cylinder, is observed to be more effective at high Reynolds number.